Treating Rheumatoid Arthritis to Target: multinational recommendations assessment questionnaire. Issue 11 (29th July 2011) - Haraoui, Boulos; Smolen, Josef S; Aletaha, Daniel; Breedveld, Ferdinand C; Burmester, Gerd; Codreanu, Catalin; Da Silva, José Pereira; de Wit, Maarten; Dougados, Maxime; Durez, Patrick; Emery, Paul; Fonseca, João Eurico; et al.
Abstract : Aim: To measure the level of agreement and application of 10 international recommendations for treating rheumatoid arthritis (RA) to a target of remission/low disease activity. Methods: A 10-point Likert scale (1=fully disagree, 10=fully agree) measured the level of agreement with each of 10 recommendations. A 4-point Likert scale (never, not very often, very often, always) assessed the degree to which each recommendation was being applied in current daily practice. If respondents answered 'never' or 'not very often', they were asked whether they would change their practice according to the particular recommendation. Results: A total of 1901 physicians representing 34 countries participated. Both agreement with and application of recommendations was high. With regard to application of recommendations in daily practice, the majority of responses were 'always' and 'very often'. A significant percentage of participants who were currently not applying these recommendations in clinical practice were willing to change their practice according to the recommendations. Conclusion: The results of this survey demonstrated great support of 'Treating RA to Target' recommendations among the international rheumatology community. Additional efforts may be needed to encourage application of the recommendations among certain clinicians who are resistant to changing their practice.